El cuestionario: el instrumento de recolección de información de la técnica de la encuesta social (2005)
ABSTRACT: The technique of social survey is based on two lines basically theoretical - methodological. On the one hand, rely on the principles of mathematical statistics, such as those that govern the relationships between population and the samples taken from her. Moreover, the technique of social survey relies on principles of communication theory, in the questioning or conversation between two partners, and respondent.